Antiretroviral Treatment Adherence Rate and Associated Factors among People Living with HIV in Dubti Hospital, Afar Regional State, East Ethiopia. (9th April 2015) - Belayihun, Bekele; Negus, Rahma
Abstract : Introduction . Antiretroviral Therapy has transformed HIV infection into a chronic manageable disease; it requires near perfect adherence rates (as high as 95%). In this study, we assessed antiretroviral treatment adherence rate and associated factors among people living with HIV in Dubti Hospital. Methods . A retrospective cross-sectional study design was conducted within February 1–30, 2014. All HIV-infected patients above the age of 18 years who took first line Antiretroviral Therapy were eligible for inclusion of the study. Adherence Scale was used for labeling patients as adherent or nonadherent. All HIV-infected patients record data were collected from the medical records, entered, and analyzed using Epi Info 7 and SPSS Version 20. Multivariable analysis was used to identify the relative effect of explanatory variables on low adherence rate. Results . A total of 370 patients aged 18 years and above, who started ART, were included in this study. The self-reported adherence rate of the patient on ART was 81.1%. Independent predictors of adherence were treatment duration. Conclusion . Adherence rate was associated with time to ART. That is, the longer they were on ART, the lesser they adhered.